The Effect of Different Techniques in Processing of Purple Yam Flour (Dioscorea alata) on The Characteristics of Mocaf-Based Cookies - Putri, Mega Bunda; Ulyarti, U; Lavlinesia, L; Mursalin, M; Purba, Daniel Tua (PUI BiGME Universitas Jambi, 2025)
The utilization of purple yam flour is expected to enhance the functional value of cookies. This study aims to determine the effect of processing techniques of purple yam flour (Dioscorea alata) on the characteristics of mocaf-based cookies. This study uses a Completely Randomized Design. Complete with treatments of various processing technique for yam flour: P1 (yam tubers are cut, then steamed, sliced, and dried), P2 (yam tubers are sliced, soaked in 1% citric acid for 30 minutes, steamed, and dried), P3 (yam tubers are cut, then soaked in water for 24 hours, sliced, and dried), P4 (yam tubers are cut, steamed, mashed, mixed with mocaf, and dried), and P5 (yam tubers are soaked in 1% citric acid for 30 minutes, steamed, mashed, mixed with mocaf, and dried). The research shows that the processing techniques affect the hedonic quality of color and flavor of the produced cookies. The encapsulation with mocaf able to retain the color of purple but appear to be darker and not preferred by the panelist. Based on the sensory analysis, the selected cookies from treatment P3 was chosen to produce yam-mocaf cookies. This cookie has color values L*, a*, b* of (37.95; 9.30; 2.10), hardness 77.76gF, moisture content 6.75%, ash content 2.22%, fat content 17.28%, protein content 6.81%, fiber content 5.48%, carbohydrate content 66.79%, and anthocyanin content of 47.01 mg/100g.